Perlindungan Hukum Terhadap Anak Sebagai Penyalahguna Narkotika (Studi Putusan Nomor 44/Pid.Sus-Anak/2019/Pn.Mdn) - Sri Wahyuni; Marlina Marlina; Rizkan Zulyadi (Mahesa Research Center, 2021)
The spread of narcotics which has spread to various levels of society and remote villages has reached children whose thinking abilities are still low. In the decision of the panel of judges not to apply diversion which refers to Article 12, Article 52 paragraph (5) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to determine the legal protection of children as narcotics abusers. The research method used is a normative juridical research with analytical descriptive character. The approach method used in this research is the case approach to the statutory approach which is carried out by examining the provisions of the applicable legislation. The analysis was carried out qualitatively. The results of the study indicate that the legal protection carried out against children as narcotics abusers in Indonesia based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System has been regulated starting from the process of investigation, arrest, detention, prosecution, examination in court and correctional. The Medan District Court has tried to carry out the legal protection process for children as narcotics abusers by referring to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. Juvenile Judges seek to realize the legal protection process by fulfilling children's rights during the examination process, as well as seeking settlement of cases through diversion. However, the efforts of juvenile judges in the legal protection process for children are still not maximized.